2011
DOI: 10.1093/ejo/cjq193
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enamel bleaching on the shear bond strengths of metal and ceramic brackets

Abstract: The aim of this study was to evaluate the effects of bleaching and delayed bonding on the shear bond strengths of metal and ceramic brackets bonded with light and chemically cure composite resin to human enamel. One hundred and twenty extracted human premolar teeth were randomly divided into three groups of 40 each. The first two groups were bleached with 20 per cent carbamide peroxide (CP) at-home bleaching agent. No bleaching procedures were applied to the third group and served as control. The first two and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
2
15
1
Order By: Relevance
“…Contrary to previous observations, 21 this study indicates that after 14 days of storage in saliva, there was a significant difference between bleached and unbleached enamel, with 10% of the influence on the shear bond strength due to the bleaching treatment. This reduction in adhesive strength after 14 days was also found by Stokes et al, 12 who used hydrogen peroxide for 2 hours on enamel.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to previous observations, 21 this study indicates that after 14 days of storage in saliva, there was a significant difference between bleached and unbleached enamel, with 10% of the influence on the shear bond strength due to the bleaching treatment. This reduction in adhesive strength after 14 days was also found by Stokes et al, 12 who used hydrogen peroxide for 2 hours on enamel.…”
Section: Discussioncontrasting
confidence: 99%
“…16,20 Enamel exposed to bleaching agents presents slight morphologic alterations, whereas phosphoric acid treatment causes severe morphologic alterations. 21 Different types and concentrations of bleaching agents have been studied. 7,12,13,22,23 Hydrogen peroxide was chosen in this study because it can penetrate into the enamel more efficiently than carbamide peroxide as a result of its lower molecular weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were in correlation with the results obtained by Chauhan et al 15 who also reported similar findings in their study. Oztaş et al 16 assessed the impact of bleaching and late bonding on the shear bond strengths of metal and ceramic brackets bonded with light and chemically cured composite resin to human teeth. They analyzed a total of 120 freshly extracted human premolars and divided them randomly into three study groups with 40 specimens in each group.…”
Section: Discussionmentioning
confidence: 99%
“…The results for the shear bond strength of the bleached groups in this study are in agreement with previous studies, in which there was no reduction in mean shear bond strength at least one week following bleaching with carbamide peroxide. [16][17][18] When analyzing the results from bonding studies, it is important to consider the minimum value in the series together with the mean values. In the 24-hour interval test series, the lowest shear bond strength in the present study was 10.13 MPa, found in the Transbond XT primer group on unbleached teeth.…”
Section: Discussionmentioning
confidence: 99%